Analysis Of Transport And Warehouse Processes Using Forecasting Method With Olympic By Management System PT. XYZ - Rionaldo Nainggolan; Wahyudin Wahyudin (Patria Artha Technological Journal, 2022)
The problems are happening at PT. XYZ regarding the work system. A good work system is a work system that has high efficiency and productivity values. So the role of industrial management is absolutely necessary in terms of designing a new system that can increase the production. Activities or linkages between elements are interdependent to achieve the same goal. In line with current problems, the purpose of this study is to determine the management of existing processes in a company that is influenced by several factors. In addition, the output also affects the efficiency of existing work productivity. The results of this study indicate that an engineering project is needed to increase the existing effectiveness. To be able to produce products with good quality and in accordance with standard operating procedures in making products. The company must carry out quality control by taking into account the level of defects produced in production. In order for the defect level of a product to be close to zero defect or if none is equal to zero, it is necessary to make a repair which of course will require quite a long time and a lot of money. By using quality control, it is hoped that a company can reduce the occurrence of defective products, and can reduce things that are not expected by the company in accordance with the vision and mission. There is a management system that can be applied, namely MBOS or better known as Management By Olympic System.